Cultivating Critical, Justice-Oriented Data Literacies in a Post-Truth World - Polman, Joseph L.; Tabak, Iris; Tran, Trang C.; Amato, Anna; Silander, Megan; Matuk, Camillia; Beale, Jill; DesPortes, Kayla; Tes, Marian; Vacca, Ralph; Woods, Peter J.; Pimentel, Daniel R.; et al. (My University, 2022)
Canada
Keywords: axiology; data literacies; data science education; epistemology; justice; post-truth